Rancang Bangun Konstruksi Rangka Dan Bak Penampung Alat Penyapu Jalan - Muhammad Ziyad; Aidil Zamri; Zulhendri Zulhendri (Jurnal Teknik Mesin, 2018)
At this time in the process of sweeping the road still using traditional tools by janitors, for example broom sticks. One of the technologies that began to develop was the Street Sweeper machine. This Street Sweeper is a tool to help alleviate the work of janitors in terms of road sweeping. Sweeping the highway using the Street Sweeper is one of the main steps to accelerate the process of sweeping the highway with rapid traffic flow. The working principle of this machine is by utilizing thrust from humans, by means of a machine being pushed and directed to the garbage scattered on the road. Therefore it is very appropriate to use Street Sweeper to sweep the road compared to using manual tools because it can save work time